The Liberal International Order and Peaceful Change: Spillover and the Importance of Values, Visions, and Passions. Issue 4 (2020) - Flockhart, Trine
Abstract: As part of the roundtable "International Institutions and Peaceful Change, " this essay focuses on the role of institutions as agents of peaceful change from a perspective that emphasizes the importance of a wide spectrum of human emotions to better understand the less quantifiable but nevertheless important conditions for being able to sustain initiatives for peaceful change. It aims to throw light on the often overlooked psychological and emotional hurdles standing in the way of agents' ability to undertake and sustain action designed to lead to peaceful change. To do so, the essay returns to the pioneering work of Ernst Haas and his important concept of "spillover." The essay shows that the neofunctional understanding of spillover was a theoretically important innovation, but that it was missing three essential elements: an understanding of the need for positive emotions and ontological security; an understanding of the link between values and identity; and a realization of the importance of a shared vision for the "good life." To illustrate the problems with Haas's version of spillover, but also to highlight the significant potential of the theory, the essay turns to the crisis of the liberal international order as an example of a forum where the agency to undertake peaceful change seems to be faltering. The essay concludes that the ability of the liberal order to effect peaceful change is currently hampered because the order is characterized by negative emotions, contested values, and a vision of the good life that is seen as mainly a benefit for the cosmopolitan elite.